Botyrosphaeria Dothidea Associated With White Rot And Stem Bark Canker Of Apple In Jammu & Kashmir (Applied Biological Research, 2010)
Apple orchards in nine locations of Kashmir valley were surveyed in 2006 and  2007 for white rot and stem canker bark disease. Maximum disease incidence  was noticed on scaffold branches and trunks of the trees. The anamorph of  causal pathogen of white rot and stem canker was identified as Fusicoccum  aesculi Corda, while the teleomorph as Botryosphaeria dothidea (Mung.Fr.) Ces.  & De Not. Botryosphaeria dothidea is reported for the first time from the  Jammu and Kashmir State.
Keywords: Apple trees; Botryosphaeria dothidea; disease incidence; Jammu & Kashmir; stem bark canker; white rot